2004
DOI: 10.4012/dmj.23.656
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Strength of Glass Ionomer Cements and Their Bond Strength to Bovine Teeth

Abstract: This study examined the possible correlation between the strength of glass ionomers and their adhesive strength to bovine teeth.The shear bond strengths of three different brands of glass Ionomer mixed at four different P/L ratios to bovine teeth were measured 24 hours after the cement specimens were prepared.The correlation between shear bond strength and mechanical strength reported in our previous study was also examined. No significant (p>0.05) increases in the bond strength to bovine teeth were found in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
0
7
1
2
Order By: Relevance
“…While a previous study showed that there was no significant correlation between mechanical strength of cement and its bond strength to bovine teeth 29 , this study yielded different results. In particular, significant correlations were observed between shear bond strength to tooth enamel and flexural strength at the immediate condition, after 24-hour storage, and after thermocycling.…”
Section: Discussioncontrasting
confidence: 50%
“…While a previous study showed that there was no significant correlation between mechanical strength of cement and its bond strength to bovine teeth 29 , this study yielded different results. In particular, significant correlations were observed between shear bond strength to tooth enamel and flexural strength at the immediate condition, after 24-hour storage, and after thermocycling.…”
Section: Discussioncontrasting
confidence: 50%
“…Therefore, the mechanical properties of cements, as well as their adhesive properties, are important factors that influence the durability of restorations in the oral cavity. The mechanical properties of dental cements have been reported in many studies [1][2][3] . In particular, several researchers have investigated the shear strength of restorative materials using the shear punch test [4][5][6][7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…E isto, provavelmente, também ocorre na dentina, de modo que o esmalte bovino é mais poroso que o esmalte humano estando presente uma alta difusão, razão do progresso da lesão de cárie artificial. Pesquisa semelhante foi feita por Hibino et al 22 quando avaliaram a força de adesão dos cimentos de ionômero de vidro ao esmalte bovino. Diaset al 23 estudaram a força de adesão de três adesivos ao esmalte bovino através do preparo com broca diamantada, broca carbide e desgaste por lixa de papel.…”
Section: Discussionunclassified
“…Apesar da força de adesão ao esmalte bovino ser 35% mais fraca quando comparada ao esmalte humano 2 , outros estudos mostraram que os dentes humanos podem ser tranqüilamente substituídos pelos dentes bovinos em muitos tipos de pesquisa, principalmente naquelas sobre colagem, adesividade e força de tração [22][23][24][25] . Por outro lado, outro estudo mostrou que a adesividade no esmalte bovino pode ser maior que em esmalte humano 30 .…”
Section: Discussionunclassified